Parasites in Loricariidae from Brazil: checklist and new records for fish from the Brazilian Amazon (Acta Scientiarum. Biological Sciences, 2018)
The aim of this study was to investigate the parasites fauna of Ancistrus leucostictus, Hypostomus ventromaculatus, Ancistrus sp. and Hemiancistrus sp. from the Igarapé Fortaleza River (Amapá State, Brazil), besides making a checklist of the parasite species in Loricariidae from Brazil. A total of 53 fishes were collected from November 2013 to August 2014. In the hosts, a total of 1,559 parasites of seven taxa were collected: Unilatus unilatus, Trinigyrus mourei, undetermined metacercariae, Genarchella gernachella, Raphidascaris (Sprentascaris) sp., Gorythocephalus elongorchis and Proteocephalus sp. Ectoparasite species were frequent in the examined Loricariidae species, which also had larval stages of endoparasites. The hosts with the highest sampled number, H. ventromaculatus and Ancistrus sp., had the highest parasite species richness. Loricariidae species from Brazil are parasitized by species of Protozoa, Monogenea, Nematoda, Digenea, Acantocephala, Cestoda, Crustacea and Hirudinea, but monogeneans, digeneans and nematodes were the predominant taxa.